GE_GERICHTE P/20958/2021 vom 14. März 2023 - GE Cour de justice (2023)
COMMERCE DE STUPÉFIANTS;CAS GRAVE;ENTRÉE ILLÉGALE;SÉJOUR ILLÉGAL;EXPULSION(DROIT PÉNAL);RÈGLEMENT (CE) 1987/2006 | LStup.19.al1; LStup.19.al2; LEI.115; CP.66a.al1